Numerical simulation of the conductivity relaxation in the high resistivity semiconductor - Pincevičius, Albertas; Meilūnas, Mečislavas; Tumanova, Natalija (Mathematical Modelling and Analysis, 2007)
A theoretical model describing the relaxation of charge carriers in semiconductors of high resistance under the influence of the laser pulses is presented. It is demonstrated that parameters of the trapping states relevant to the processes of the conductivity relaxation can be defined by fitting the experimental data. Time evolution of the conductivity of the GaAs bulk semiconductor under the influence of nanosecond and picosecond laser pulses is considered. Effect of two laser pulses, when the first one results in population of the trapping state and the second one induces its depopulation, is also considered. First Published Online: 14 Oct 2010